The Effect of Competence and Work Environment on Employee Performance (Case Study on Village Apparatus in Telukjambe Timur District, Karawang Regency): Human Resource Management - Wiwin Agustina Widiyanti; Cecep Hermana (Fakultas Bisnis, 2022)
This study means to decide the impact of skill and workplace on worker execution in town authorities in Teluk Jambe Timur sub-region, both somewhat and all the while. the technique utilized is confirmation with a quantitative methodology where the information is handled utilizing SPSS programming. The example utilized in this study was 110 examples utilizing immersed examining procedure. The information investigation utilized is way examination with incomplete and concurrent speculation testing. The consequences of this study are that there is a connection among skill and workplace of 0.114, and that truly intends that there is an extremely frail relationship. There is a halfway impact of skill on worker execution. There is a fractional impact of workplace on representative execution. There is a concurrent impact of skill and workplace on execution of 30.1%. This shows that skill and workplace have a commitment of 30.1% while the excess sum is the commitment of different factors not analyzed in this review.